Case reportInfantile mitochondrial leucodystrophy – a case report - Schmidt-Sidor, Bogna; Szymańska, Krystyna; Lewandowska, Eliza; Mierzewska, Hanna; Wierzba-Bobrowicz, Teresa; Pasennik, Elżbieta; Stępień, Tomasz (Folia Neuropathologica, 2005)
We retrospectively analyzed a case of a 7-month-old infant with a delay of psychomotor development, slow pupillary light reflexes, horizontal nystagmus, spasticity and bilateral optic nerve atrophy. At the end of life there were problems with swallowing. Ventriculography showed widening of the lateral ventricles and atrophy in the frontal lobes. EEG revealed generalized changes. Clinically, leucodystrophy was diagnosed. General autopsy revealed cardiac hypertrophy. Neuropathological picture showed orthochromatic leucodystrophy with some features characteristic of neuropathology of mitochondrial disease: capillary hyperplasia and hypertrophy, spongiosis and symmetrical, bilateral damage of brain stem structures. The last one is characteristic of Leigh syndrome. Electron microscopic evaluation showed abnormal mitochondria, myelin and neurofibrils destruction. Hypertrophy of the heart may be also connected with mitochondrial disease.